Soil microbial legacies influence plant survival and growth in mine reclamation - Katie McMahen; Shannon H. A. Guichon; C. D. Anglin; Les M. Lavkulich; Susan J. Grayston; Suzanne W. Simard (Ecology and Evolution, 2022)
Abstract Plants alter soil biological communities, generating ecosystem legacies that affect the performance of successive plants, influencing plant community assembly and successional trajectories. Yet, our understanding of how microbe‐mediated soil legacies influence plant establishment is limited for primary successional systems and forest ecosystems, particularly for ectomycorrhizal plants. In a two‐phase greenhouse experiment using primary successional mine reclamation materials with or without forest soil additions, we conditioned soil with an early successional shrub with low mycorrhizal dependence (willow, Salix scouleriana) and a later‐successional ectomycorrhizal conifer (spruce, Picea engelmannii × glauca). The same plant species and later‐successional plants (spruce and/or redcedar, Thuja plicata, a mid‐ to late‐successional arbuscular mycorrhizal conifer) were grown as legacy‐phase seedlings in conditioned soils and unconditioned control soils. Legacy effects were evaluated based on seedling survival and biomass, and the abundance and diversity of root fungal symbionts and pathogens. We found negative intraspecific (same‐species) soil legacies for willow associated with pathogen accumulation, but neutral to positive intraspecific legacies in spruce associated with increased mycorrhizal fungal colonization and diversity. Our findings support research showing that soil legacy effects vary with plant nutrient acquisition strategy, with plants with low mycorrhizal dependence experiencing negative feedbacks and ectomycorrhizal plants experiencing positive feedbacks. Soil legacy effects of willow on next‐stage successional species (spruce and redcedar) were negative, potentially due to allelopathy, while ectomycorrhizal spruce had neutral to negative legacy effects on arbuscular mycorrhizal redcedar, likely due to the trees not associating with compatible mycorrhizae. Thus, positive biological legacies may be limited to scenarios where mycorrhizal‐dependent plants grow in soil containing legacies of compatible mycorrhizae. We found that soil legacies influenced plant performance in mine reclamation materials with and without forest soil additions, indicating that initial restoration actions may potentially exert long‐term effects on plant community composition, even in primary successional soils with low microbial activity.